2019
DOI: 10.3389/fonc.2019.00504
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation Between the Inflammation and Coagulation Systems Promotes the Survival of Circulating Tumor Cells in Renal Cell Carcinoma Patients

Abstract: Most renal cell carcinoma (RCC) patients die from metastasis or recurrence after the spread of cancer to another organ, but the mechanisms underlying the intravascular survival of circulating tumor cells (CTCs) have not been completely deciphered. Additionally, although elevated plasma C-reactive protein (CRP) levels and thrombocytosis are strongly correlated and both indicate a poor prognosis for RCC patients, the bridge connecting inflammation and coagulation remains poorly understood. To explore the complic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 59 publications
1
33
0
Order By: Relevance
“…Supporting these experimental data, NETs have been associated with a poor prognosis in several cancer types and with cancer-associated VTE [260,261]. Recapitulating these relationships in renal cell carcinoma patients, Wen et al reported that a high CTC count correlates with elevated levels of fibrinogen and RNA expression of NET's markers in blood leukocytes [262].…”
Section: Interaction With Neutrophilsmentioning
confidence: 86%
“…Supporting these experimental data, NETs have been associated with a poor prognosis in several cancer types and with cancer-associated VTE [260,261]. Recapitulating these relationships in renal cell carcinoma patients, Wen et al reported that a high CTC count correlates with elevated levels of fibrinogen and RNA expression of NET's markers in blood leukocytes [262].…”
Section: Interaction With Neutrophilsmentioning
confidence: 86%
“…2 Inflammation is a hallmark of cancer, and malignant tumors compromise the coagulation, anticoagulation, and fibrinolysis systems of the body through various mechanisms, resulting in abnormal coagulation function and fibrinogen elevation. 3 Fibrinogen is an acute-phase-response protein that can increase under systemic inflammatory conditions. Previous studies have shown that increased plasma fibrinogen indicates poor prognosis of various cancers including GC.…”
Section: Introductionmentioning
confidence: 99%
“…28 Our previous research also pointed out that the abnormality of inflammation and coagulation indexes is correlated with viable CTCs, which is the premise of tumor recurrence and metastasis, and the neutrophil extracellular traps (NETs) induced by circulating neutrophils could protect the survival of circulating tumor cells, thus promoting postoperative recurrence and metastasis in patients with RCC. 11 Therefore, it is reasonable to construct a prognostic model for local renal cell carcinoma based on the combination of hematological indicators FIB, CRP, and NLR.…”
Section: Discussionmentioning
confidence: 99%
“…We have reported that the plasma concentrations of FIB, CRP and neutrophils were positively correlated with the circulating tumor cells (CTCs), which was a prerequisite for recurrence and metastasis. 11 In this study, we evaluated the preoperative blood indexes to explore a risk classification for predicting disease-free survival (DFS) in patients with stage I-III ccRCC. The inclusion criteria of the study were as follows: (1) no primary cancer of any other organs before the operation; (2) no chronic inflammatory allergic disease; (3) no history of taking anticoagulants such as for cardiovascular or cerebrovascular thrombosis; (4) exact pathological diagnosis of ccRCC; (5) complete resection of the tumor, which was defined as a negative incisal margin; (6) complete clinicopathological characteristics and follow-up data; and (7) no evidence of extrarenal metastasis.…”
Section: Introductionmentioning
confidence: 99%